2015
DOI: 10.1128/mcb.00087-15
|View full text |Cite
|
Sign up to set email alerts
|

RBM45 Modulates the Antioxidant Response in Amyotrophic Lateral Sclerosis through Interactions with KEAP1

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by the selective loss of motor neurons. Various factors contribute to the disease, including RNA binding protein dysregulation and oxidative stress, but their exact role in pathogenic mechanisms remains unclear. We have recently linked another RNA binding protein, RBM45, to ALS via increased levels of protein in the cerebrospinal fluid of ALS patients and its localization to cytoplasmic inclusions in ALS motor neurons. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 62 publications
(80 reference statements)
1
16
0
Order By: Relevance
“…This localization was consistent with that of endogenous Drb1 protein reported previously in human neuronal cells (22,24) or T7-tagged Drb1 (Fig. 1B).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This localization was consistent with that of endogenous Drb1 protein reported previously in human neuronal cells (22,24) or T7-tagged Drb1 (Fig. 1B).…”
Section: Resultssupporting
confidence: 92%
“…Using a yeast two-hybrid system, it was determined that the carboxyl-terminal region of TDP-43 interacts with Drb1 (23). Drb1 is also redistributed from the nucleus to the cytoplasm by oxidative stresses such as H 2 O 2 and paraquat and modulates the antioxidant response via cytoplasmic interaction with Kelch-like ECH-associated protein 1 (KEAP1), an inhibitor of the antioxidant response transcription factor nuclear factor erythroid 2-related factor 2 (NRF2) (24). Despite these findings in relation to ALS pathology, the mechanism underlying the formation of Drb1 cytoplasmic aggregation remains unclear.…”
mentioning
confidence: 99%
“…Intriguingly, proteins that associate with KEAP1 impact KEAP1 stability without disrupting the KEAP1-NRF2 binding interface. For example, RNA-binding motif 45 (RBM45) is known to bind and stabilize KEAP1 protein in motor neurons with amyotrophic lateral sclerosis (102). Although changes in RBM45 expression in tumors have not been extensively studied, recent proteomic studies examining reactive cysteines in KEAP1-mutant non-small cell lung cancer cell lines revealed protein-protein interactions between the cysteine-reactive nuclear factor receptor subfamily 0 group B member 1 (NR0B1) and RBM45 (103).…”
Section: V334 S363mentioning
confidence: 99%
“…Recent studies identified co-localization of TDP-43 and RNA-binding motif-45 (RBM45) inclusions and their RNA-dependent association in motor neurons of some cases of ALS (Collins et al, 2012; Mladinic et al, 2010). Like TDP-43, RBM-45 is mainly nuclear, but migrates to cytoplasm and co-localizes in SGs to associate with Kelch-like ECH-Associated protein 1, a component of anti-oxidant machinery (Bakkar et al, 2015). Furthermore, TDP-43 co-localizes in cytoplasmic inclusions with Poly-A binding protein - 1 (PABP-1); a stress granules marker (McGurk et al, 2014).…”
Section: Introductionmentioning
confidence: 99%